Characteristics of aerobic capacity during submaximal arm cranking in sitting para-athletes with and without spinal cord injury - Kameda, M.; Iizuka, S.; Hakamada, N.; Ishige, Y. (Japan Journal of Physical Education, Health and Sport Sciences, 2025)
This study aimed to examine the submaximal aerobic capacity of elite sitting para athletes with and without spinal cord injury. The participants were Japanese elite para-athletes, including six badminton players, seven wheelchair tennis players, and eleven alpine ski players (age: 30 (16-46) yrs, body height or arm span: 169.1 (141.9- 185.1) cm, weight: 56.2 (37.3-83.3) kg). Participants were divided into two groups: those with spinal cord injuries (SCI, n = 12) and those without (OPA, n = 12). Body mass, lean body mass, and body fat percentage were measured using an air displacement plethysmograph (BODPOD). The participants performed an incremental arm cranking test until their blood lactate concentration exceeded 4 mmol/L. The test protocol for blood lactate concentration was determined based on the participants` events and sex. We evaluated the workload and heart rate at the Lactate Threshold (LT) and the Onset of Blood Lactate Accumulation (OBLA) during the incremental arm cranking test. There were no significant differences between SCI vs. OPA in the workload 52.2 (17.0-70.0) W vs. 54.0 (16.0-82.0) W at LT, and 82.5 (39.6-108.0) W vs. 78.4 (36.0-124.6) W at OBLA and heart rate 119.5 (104.0-138.0) bpm vs. 120.4 (91.0- 139.5) bpm at LT, and 149.2 (131.0-165.4) bpm vs. 150.5 (127.0-170.0) bpm at OBLA. The present study indicates that, in terms of workload and heart rate at LT and OBLA, elite sitting para-athletes with spinal cord injuries have aerobic capacities similar to those of athletes without spinal cord injuries.